Ergogenic aids to improve physical performance in female athletes: A systematic review with meta-analysis - López-Torres, O.; Rodríguez-Longobardo, C.; Capel-Escoriza, R.; Fernández-Elias, V. E. (Nutrients, 2023)
Most intervention studies investigating the effects of ergogenic aids (EAs) on sports performance have been carried out in the male population. Thus, the aim of this systematic review and meta-analysis was to summarize the effects in the existing literature of EAs used by female athletes on performance. A literature research was conducted, and a descriptive analysis of the articles included in the systematic review was carried out. Meta-analyses could be performed on 32 of the included articles, evaluating performance in strength, sprint, and cardiovascular capacity. A random-effects model and the standardized mean differences (SMD) ± 95% confidence intervals (CI) were reported. The results showed that caffeine helped to improve jumping performance, isometric strength values, and the number of repetitions until failure. Caffeine and sodium phosphate helped to improve sprint performance. Aerobic tests could be improved with the use of taurine, caffeine, and beta-alanine. No conclusive effects of beetroot juice, polyphenols, or creatine in improving aerobic performance were shown. In terms of anaerobic variables, both caffeine and sodium phosphate could help to improve repeated sprint ability. More studies are needed in female athletes that measure the effects of different EAs on sports performance, such as beetroot juice, beta-alanine or sodium phosphate, as the studies to date are scarce and there are many types of EA that need to be further considered in this population, such as creatine and taurine